Scale and confinement phase transitions in scale invariant SU(N) scalar gauge theory - Kubo, Jisuke; Yamada, Masatoshi (Journal of high energy physics, 2018)
We consider scalegenesis, spontaneous scale symmetry breaking, by the scalar-bilinear condensation in SU(N) scalar gauge theory. In an effective field theory approach to the scalar-bilinear condensation at finite temperature, we include the Polyakov loop to take into account the confinement effect. The theory with N = 3, 4, 5 and 6 is investigated, and we find that in all these cases the scale phase transition is a first-order phase transition. We also calculate the latent heat at and slightly below the critical temperature. Comparing the results with those obtained without the Polyakov loop effect, we find that the Polyakov effect can considerably increase the latent heat in some cases, which would mean a large increase in the energy density of the gravitational waves background, if it were produced by the scale phase transition.